The Role of Higher Education in Driving Innovation and Economic Growth: Literature Review - Saringatun Mudrikah; Muhammad Sabandi; Lukman Hakim (Universitas Negeri Semarang, 2026)
Higher education is a primary pillar of modern economic development, playing a crucial role in knowledge development, human capital formation, and innovation creation. In a knowledge-based economy, universities function not only as educational institutions but also hold a strategic role in research, technological innovation, and cross-sector collaboration through models such as the Multi-Helix. This study employs a Systematic Literature Review (SLR) approach and bibliometric analysis using the PRISMA method on 128 Scopus-indexed articles from the 2015–2025 period. The analysis was conducted to map publication trends, geographical distribution, collaboration networks, and key research themes using VOSviewer software. The results indicate that publication trends increased significantly after 2022, reaching a peak in 2024, with dominant contributions from European countries, particularly the United Kingdom, as well as China, Italy, and Spain. Central themes dominating the literature include